2022
DOI: 10.3389/fnagi.2022.975068
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gait in Parkinson’s disease is associated with the microstructural and functional changes of globus pallidus internus

Abstract: BackgroundFreezing of gait (FOG) is a common motor symptom in advanced Parkinson’s disease (PD). However, the pathophysiology mechanism of FOG is not fully understood. The purpose of this study was to investigate microstructural abnormalities in subcortical gray matter and alterations in functional connectivity of the nuclei with microstructural changes. In addition, the correlations between these microstructural and functional changes and the severity of FOG were measured.Materials and methodsTwenty-four pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…Recent studies have showed that diffusion changes in the globus pallidus are associated with FOG. 39,40 Within the landscape of susceptibility MRI studies in PD investigating the relationship between susceptibility and gait, our study aligns with another study demonstrating susceptibility changes in the putamen and globus pallidus. 10 Our study complements these susceptibility and diffusion MRI studies by showing that susceptibility changes in the globus pallidus are also implicated in FOG.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recent studies have showed that diffusion changes in the globus pallidus are associated with FOG. 39,40 Within the landscape of susceptibility MRI studies in PD investigating the relationship between susceptibility and gait, our study aligns with another study demonstrating susceptibility changes in the putamen and globus pallidus. 10 Our study complements these susceptibility and diffusion MRI studies by showing that susceptibility changes in the globus pallidus are also implicated in FOG.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have showed that diffusion changes in the globus pallidus are associated with FOG. 39,40…”
Section: Discussionmentioning
confidence: 99%
“…The direct pathway facilitates the intended movements, while the indirect pathway inhibits the neural responses of the thalamus, making excitation of the motor cortex less likely, hence inhibiting action. Studies of Parkinson's disease have shown that patients are characterized by slowness of movement (bradykinesia), possibly due to dysfunction in the direct pathway [22][23][24][25][26][27]29,30]. Conversely, Huntington's disease is associated with rapid, jerky motions with no clear purpose, possibly due to dysfunction in the indirect pathway [22].…”
Section: Introductionmentioning
confidence: 99%